Studi Fenomenologi Persepsi Pasien dan Keluarga tentang Luka Kaki Diabetes - Idramsyah, Idramsyah; Novira, Daisy (Health Information : Jurnal Penelitian, 2023)
The condition of diabetic foot ulcers has various accompanying problems such as wounds that don't heal, wound odor, and lots of wound exudate, even the threat of amputation and disability. Patient and family responses vary greatly to the diabetic foot ulcers they experience. This study aims to explore patient and family perceptions of diabetic foot ulcers. This research is a type of qualitative research using a phenomenological approach. In-depth interviews were conducted with 12 participants who were family and patients with chronic diabetic foot ulcers. Data that has been analyzed verbatim with the Colaizi stage. The results of this study formulated 4 themes, namely (1) the predispose of diabetic foot ulcers is simple but complex, (2) all people with DM are at risk of developing diabetic foot ulcers, (3) people with foot injuries diabetes threaten the threat of disability and amputation, (4) diabetic foot ulcers cause a lot of burden. People with diabetic foot ulcers have positive and negative perceptions of their wounds. The impact of the perceptions that are believed to the wound healing process needs to be further identified.